Réponses

  • Utilisateur Brainly
2013-06-24T12:12:05+02:00

1)

{3x + 5y + 5 = 0
{x - y -1 = 0

 

donc

{3x+5y=-5

{x-y=1

 

donc

{3x+5y=-5

{5x-5y=5


donc par somme : 8x=0 donc x=0

alors 0-y=1 donc y=-1

donc S={(0;-1)}

 

2)
{3x - y = -1
{5x + 3y = -11

 

donc

{9x-3y=-3

{5x+3y=-11

 

donc par somme : 14x=-14 donc x=-1

alors -3-y=-1 donc y=-2

donc S={(-1;-2)}

2013-06-24T14:59:34+02:00

3x + 5y + 5 = 0

x - y -1 = 0

 

3x + 5y= - 5

x - y= 1

 

3x + 5y= - 5

x= 1 + y

 

3(1 + y) + 5y= - 5

x= 1 + y

 

3 + 3y + 5y= - 5

x= 1 + y

 

3 + 8y= - 5

x= 1 + y

 

8y= - 5 - 3

x= 1 + y

 

8y= - 8

x= 1 + y

 

y=

 

 

 

 

 

 

 

1)

{3x + 5y + 5 = 0 {x - y -1 = 0

 

donc

{3x+5y=-5

{x-y=1

 

donc

{3x+5y=-5

{5x-5y=5

donc par somme : 8x=0 donc x=0

alors 0-y=1 donc y=-1

donc S={(0;-1)}

 

2) {3x - y = -1 {5x + 3y = -11

 

donc

{9x-3y=-3

{5x+3y=-11

 

donc par somme : 14x=-14 donc x=-1

alors -3-y=-1 donc y=-2

donc S={(-1;-2)}